The theoretical analysis of the interaction between methane dehydrogenation and carbon dioxide dissociation products with Ni and PtNi surfaces - Ayvaz, Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Catalytic Dry Reforming of Methane (CDRM), in general sense, involves simultaneous carbon dioxide disproportionation yielding carbon monoxide and surface oxygen, methane dehydrogenation yielding hydrogen, CHx groups and surface carbon, and, finally, reaction between surface oxygen and surface carbon that cleans the surface yielding carbon monoxide. The aim of this study is to investigate the adsorption properties of carbon dioxide and the products formed upon its dissociation, carbon monoxide and oxygen, on Ni(111) and PtNi(111) surfaces, and forming a vibrational frequency data base for methane dehydrogenation and carbon dioxide disproportination products adsorbed on Ni(111) and PtNi(111) surfaces via utilizing ab initio Dmol3 tool box of Accelrys Material Studio. Carbon dioxide adsorption properties was studied by placing carbon dioxide molecules on each possible adsorption sites of Ni(111) and PtNi(111) surface alloy. On both surfaces carbon dioxide adsorption energy values obtained were very close to zero due to the high amount of energy consumed during configurational change. Results of this study shows that adsorption of carbon dioxide is stronger on PtNi(111) surface alloy compared to the adsorption on Ni(111) surface. The most preferred adsorption site of carbon dioxide is bridge site both for Ni(111) surface and PtNi(111) surface alloy. Adsorptions of carbon monoxide molecule and oxygen atom were also studied on Ni(111) metal. Very strong adsorption of carbon monoxide and oxygen on Ni surface was verified. Calculated frequency data base, which is consistent with the experimental data in the literature, was tabulated and will be furtherly used in determination of the catalytically active adsorption sites on Ni and PtNi catalysts during CDRM reaction through comparative analysis of experimental FTIR-DRIFT studies performed on Ni/Al2O3 and Pt-Ni/Al2O3 catalysis.
Keywords: Carbon dioxide mitigation.; Methane.